1998
DOI: 10.1002/(sici)1096-8628(19980508)81:3<216::aid-ajmg2>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for genetic linkage to alcohol dependence on chromosomes 4 and 11 from an autosome-wide scan in an american indian population

Abstract: To identify specific genes affecting vulnerability or resistance, we performed a whole-autosomal genome scan for genetic linkage to alcohol dependence in a Southwestern American Indian tribe. Genotypes at 517 autosomal microsatellite loci and clinical evaluations were available for 152 subjects belonging to extended pedigrees and forming 172 sib-pairs. Highly suggestive evidence for linkage emerged for two genomic regions using two- and multipoint sib-pair regression methods; both regions harbored neurogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
277
5
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(300 citation statements)
references
References 27 publications
17
277
5
1
Order By: Relevance
“…After the complete set of 10 000 pedigrees was simulated, the F-ratio above which the most extreme ␣100% of the simulated statistics lay was the empirical ␣100% significance level. With this procedure, [37][38][39] each random pedigree maintains the genotype and phenotype correlation structure that was inherent in the original sample, but there is no relationship between the genotype and phenotype, as stipulated by the null hypothesis.…”
Section: Pedigree Randomization Analysismentioning
confidence: 99%
“…After the complete set of 10 000 pedigrees was simulated, the F-ratio above which the most extreme ␣100% of the simulated statistics lay was the empirical ␣100% significance level. With this procedure, [37][38][39] each random pedigree maintains the genotype and phenotype correlation structure that was inherent in the original sample, but there is no relationship between the genotype and phenotype, as stipulated by the null hypothesis.…”
Section: Pedigree Randomization Analysismentioning
confidence: 99%
“…Two genome-wide scans in humans provided evidence of linkage of alcohol dependence to a region of chromosome 4p that includes a cluster of four genes encoding GABA A receptor subunits (Reich et al, 1998;Long et al, 1998). Edenberg et al (2004), by fine mapping this region, found that numerous single-nucleotide polymorphisms (SNPs) in the gene encoding the GABA A a-2 subunit (GABRA2), but not in other members of the gene cluster, were associated with alcohol dependence.…”
Section: Introductionmentioning
confidence: 99%
“…In other investigations of interest to the current study, cigarette smoking with or without AD, were linked to broad regions of chromosomes 9 and 11. [4][5][6][7][8][9] Among the candidate addiction susceptibility genes defined by these linkage signals were those that encode the neurotrophin, brainderived neurotrophic factor (BDNF, chromosome 11), and its cognate receptor, neurotrophic tyrosine kinase receptor B (TrkB) (NTRK2, chromosome 9).…”
Section: Introductionmentioning
confidence: 99%